Pengaruh relaksasi dzikir terhadap kecemasan menghadapi ujian online SMP Negeri 12 Makassar - yusran, Masniah (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2016)
This this research are to: (a) discover the description of the students’ anxiety level in facing online exams before and after implementing  dzikir relaxation technique , (b) discover the influence of dzikir relaxation technique to reduce students’ anxiety in facing online exams . This research employs quantitative approach with experiment type which examines on dzikir relaxation technique to reduce student’s anxiety in facing online exams. The design model of this research is pretest- posttest control group design. The results of the research reveal that: (a) the description of the student’s anxiety level in facing online exams at experiment group before implementing dzikir relaxation technique is in high category; however, after implementing dzikir relaxation technique, the students’ anxiety level in facing  online exams is in low category. In contrast, the control group which is not given a dzikir relaxation technique does not show significant change or decrease, or it is still in high category, (b) there is significant influence of dzikir relaxation technique on students’ anxiety in facing online exams at SMPN 12 in Makassar, meaning that the more dzikir relaxation techniques are given, the more decreasing students’ anxiety in facing online exams.